Real-world clinical treatment outcomes in Chinese non-small cell lung cancer with EGFR exon 20 insertion mutations - Shi, Chao; Xing, Ruyue; Li, Mengmeng; Feng, Junnan; Sun, Rui; Wei, Bing; Guo, Yongjun; Ma, Jie; Wang, Huijuan (Frontiers in Oncology, 2022)
Background EGFR exon 20 insertions (EGFR ex20ins) constitute a heterogeneous subset of EGFR-activating alterations. However, the effectiveness of standard therapy in patients with EGFR ex20ins remains poor. Methods In our study, we retrospectively collected next-generation sequencing (NGS) data from 7,831 Chinese NSCLC patients and analyzed the relationship between EGFR ex20ins variations and medical records. Results Our data showed that EGFR ex20ins account for up to 3.5% of all EGFR mutation non-small-cell lung cancer (NSCLC) patients and 1.6% of all NSCLC patients in China. Thirty-eight different variants of EGFR ex20ins were identified in 129 NSCLC patients. We observed that the patients with EGFR ex20ins may benefit from the anti-angiogenesis agents significantly (P = 0.027). In the EGFR ex20ins near-loop group, patients who received second-/third-generation EGFR-TKI therapy treatment as first-line treatment had a longer median progression-free survival (PFS) than those who initiated treatment with first-generation EGFR-TKI or chemotherapy. Patients with co-mutations of EGFR ex20ins near-loop and TP53 tended to have a shorter OS in second-/third-generation EGFR-TKI therapy (P = 0.039). Additionally, median PFS was significantly longer in patients harboring EGFR ex20ins far-loop variants who received chemotherapy as a first-line setting (P = 0.037). Conclusions Overall survival was significantly longer in EGFR ex20ins patients with anti-angiogenesis agents. For the choice of first-line strategy, NSCLC with EGFR ex20ins near-loop variants may benefit from second-/third-generation EGFR-TKI, while patients harboring EGFR ex20ins far-loop variants might have better outcomes from chemotherapy. TP53 could serve as a potential predictive marker in poor prognosis for EGFR ex20ins near-loop patients.